Postprandial nitrogen metabolism and excretion in the marble goby, Oxyleotris marmorata, in freshwater or brackish water, and/or in the presence of environmental ammonia - Chew, Shit Fun. (2010)
The marble goby, O. marmorata, is a facultative air-breather capable of growing to >1 kg, and is considered a delicacy over much of eastern Asia. Feeding led to only a slight increase in plasma ammonia concentration and had no significant effect on the ammonia content in the brain of juvenile O. marmorata during the subsequent 24 h. Unlike other fishes, juvenile O. marmorata could apparently avoid postprandial ammonia toxicity, and as a result there was no increase in the brain glutamine content, which decreased significantly instead at certain post-feeding time point. Since no prominent increases in tissue glutamine and urea contents were observed after feeding despite its ability to detoxify ammonia to glutamine during emersion and its possession of a full complement of hepatic ornithine-urea cycle enzymes, it can be concluded that only a moderate amount of ammonia was produced after feeding. Traditionally, it has been accepted that excess amino acid would be degraded in the liver through transdeamination which involves the deamination of glutamate catalyzed by glutamate dehydrogenase (GDH).